Engineering biodiversity as a model for the species conservation - ELIBIO L. RECH (Anais da Academia Brasileira de Ciências)
Abstract: Early humans have domesticated plant and animal species based on ancient empirical concepts (Darwin 1868, 1876). In 1886, Mendel established a new paradigm of hereditary laws (Mendel 1866, 1870, 1950) based on genotypic and phenotypic traits of cross-compatible species, establishing a complex breeding technology that is currently utilized for the development of most food and livestock-derived products. Recently, studies on deciphering the double-helical structure (Watson and Crick 1953a, b) and how to restrict DNA (Arber 2012) have established the foundation of recombinant DNA technology. A new era is paving the way for genetic manipulation of important traits among all the kingdom’s organisms, allowing for the development of innovative and widely utilized products for the agricultural, industrial and pharmaceutical production sectors (Mc Elroy 2003, 2004, ISAAA 2016).